2010
DOI: 10.1262/jrd.10-036k
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Adipsin, a Complement Activating Factor, in the Mouse Placenta During Spontaneous Abortion

Abstract: Abstract. The complement system is thought to be precisely regulated during pregnancy. We have examined specific gene profiles in mouse placentas causing spontaneous abortion and found notable up-regulation of adipsin, a complement activating factor. The aim of the present study was to determine the basic kinetics and localization of adipsin in the placenta and the difference in complement activity between normal placentas and placentas of abortuses. Normal and spontaneously absorbed implantation sites obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Previous studies in mice have demonstrated a significant rise in the adipsin levels in aborted placenta. Adipsin is related with the activation of complement pathway, in the decidua fibroblast, which helps with the activation of the defense mechanisms of the extracellular placental tissue 60 . In humans and murines, the activation of C3 and C4 is regulated by DAF and MCP, while in mice, Crry protein participates in this regulation 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in mice have demonstrated a significant rise in the adipsin levels in aborted placenta. Adipsin is related with the activation of complement pathway, in the decidua fibroblast, which helps with the activation of the defense mechanisms of the extracellular placental tissue 60 . In humans and murines, the activation of C3 and C4 is regulated by DAF and MCP, while in mice, Crry protein participates in this regulation 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In humans and murines, the activation of C3 and C4 is regulated by DAF and MCP, while in mice, Crry protein participates in this regulation 8 . In endometrial samples from mouse miscarriages and human placentas, the expression of DAF, MCP, and Crry proteins has been demonstrated 60 61 . Recently, it has been demonstrated in CBA/J×DBA/2 model mice a significant elevation in serum and placenta adipsin levels and that these levels are related to spontaneous abortion 62 .…”
Section: Discussionmentioning
confidence: 99%
“…A characteristic part of these changes seems to be an activation of the innate immune system, including the complement system and natural killer cells [83, 84, 86]. Adipsin (also known as Complement factor D, coded by CFD , upregulated in PREG heifers), has been subject to extra interest as it has been associated with pre-eclampsia and abortion [8789]. Consequently it seems complement activation may be part of both physiological and pathological immune changes related to pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Well-defined pathological processes include destruction of fetal erythrocytes (Rh antigen, erythroblastosis) and platelets (Human platelet alloantigens (HPA)-1 and HPA-2, alloimmune thrombocytopenia) by maternal antibodies and infections during pregnancy, where activated macrophages secreting high levels of Th1-type cytokines alter the fragile cytokine balance at the maternal-fetal interface [20, 103]. Takeshita et al found that adipsin immunoreactivity was detected either at the decidua basalis in normal placentas or at the placental maze in absorbed placentas [104]. However, they also showed that the quantity of adipsin was increased in the absorbed placentas compared with the normal placentas, suggesting that local expression of adipsin has an effect at the maternal-fetal interface and probably plays a role in spontaneous abortion [104].…”
Section: Immunomodulatory Molecules In Threatened Pregnancymentioning
confidence: 99%
“…Takeshita et al found that adipsin immunoreactivity was detected either at the decidua basalis in normal placentas or at the placental maze in absorbed placentas [104]. However, they also showed that the quantity of adipsin was increased in the absorbed placentas compared with the normal placentas, suggesting that local expression of adipsin has an effect at the maternal-fetal interface and probably plays a role in spontaneous abortion [104]. …”
Section: Immunomodulatory Molecules In Threatened Pregnancymentioning
confidence: 99%